CRISPR Cas Genome Editing Applications in Medicine and Agriculture: Aplikasi Pengeditan Genom CRISPR-Cas dalam Kedokteran dan Pertanian - Zainab Nader Hussein AlHusseini (Academia Open, 2026)
General Background Genome editing has become a central approach in modern biotechnology for modifying genetic material with high precision. Specific Background CRISPR/Cas systems have emerged as widely adopted tools in medical research, plant breeding, and sustainable food production due to their accuracy and adaptability. Knowledge Gap Despite extensive studies, there remains a need for an integrated synthesis that connects technological development, application domains, and associated challenges within a sustainability-oriented framework. Aims This article aims to review CRISPR/Cas genome-editing technologies, their applications in health and agriculture, and the challenges related to biosafety and regulation. Results The review demonstrates that CRISPR/Cas systems support disease modeling, gene therapy research, crop improvement, and biofortification, while also presenting technical and ethical constraints. Novelty The novelty lies in combining medical, agricultural, and sustainability perspectives within a single analytical framework. Implications The findings support informed research development and policy discussion regarding responsible genome-editing adoption. Keywords: CRISPR Cas Systems, Genome Editing, Gene Therapy, Plant Biotechnology, Sustainable Food Production Key Findings Highlights: Genome-editing systems enable precise modification across medical and agricultural contexts Technical challenges and biosafety considerations remain central research concerns Integrated perspectives support sustainability-oriented biotechnology development